Typology, Dynamics, and Potential Disaster in The Coastal Area District Karst Gunungkidul - Muh Aris Marfai; Ahmad Cahyadi; Dini Feti Anggraini (Universitas Muhammadiyah Surakarta, 2013)
This study aims to determine the typology, dynamics and potential disasters in the coastal area of Gunungkidul, Yogyakarta Special Province. The results showed that the typology formed in the coastal region is structurally shaped karst Gunungkidul coast, Wave Erotion Coast, marine deposition coast, coast erosion land, coast and sub-aerial deposition of man-made coastal typology. Coastal dynamics that occur in karst Gunungkidul coastal areas affected by dominant geodinamic processes, hydrodynamic and antropodinamic. There are several potential disaster in the karst Gunungkidul coastal region, namely tsunami, rip currents, abrasion, and waves reflection.